The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s00296-013-2710-7
|View full text |Cite
|
Sign up to set email alerts
|

DPP4 inhibitor-induced polyarthritis: a report of three cases

Abstract: Dipeptidyl peptidase-4 (DPP4) inhibitors are a novel therapy widespread used in type 2 diabetes mellitus. We describe 3 cases of polyarthritis which delay of appearance strongly suggests a link with DPP4 inhibitors. Three patients presented with bilateral, symmetrical, seronegative polyarthritis after introduction of DPP4 inhibitors (sitagliptine (n = 2) and vildagliptine (n = 1)). Two patients also developed xerostomia and xerostomia, and laboratory test results showed normal values of CRP and erythrocyte sed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 8 publications
0
28
0
Order By: Relevance
“…The involvement of CD26/DPP4 in arthritis has been reviewed recently, involving glycosylation and DPP4 autoantibodies on one hand and SDF‐α on the other hand . Additionally, one study summarizes three cases of DPP4 inhibitor‐induced polyarthritis .…”
Section: Involvement Of Cd26/dpp4 In Pathologymentioning
confidence: 98%
“…The involvement of CD26/DPP4 in arthritis has been reviewed recently, involving glycosylation and DPP4 autoantibodies on one hand and SDF‐α on the other hand . Additionally, one study summarizes three cases of DPP4 inhibitor‐induced polyarthritis .…”
Section: Involvement Of Cd26/dpp4 In Pathologymentioning
confidence: 98%
“…However, when data from these large trial was pooled, there was a significantly increased risk for pancreatitis in the DPP‐4 inhibitor treated patients (OR 1.79; 95% CI 1.13‐2.82, P = .013), yet the absolute risk increase was small (0.13%) . Dipeptidyl peptidase‐4 inhibitors have also been associated with polyarthritis, which seems to be reversible upon discontinuation of therapy …”
Section: Safetymentioning
confidence: 99%
“…95% CI 1.13-2.82, P = .013), yet the absolute risk increase was small (0.13%). 96 Dipeptidyl peptidase-4 inhibitors have also been associated with polyarthritis, 97,98 which seems to be reversible upon discontinuation of therapy. 98 In May 2016, the US Food and Drug Administration issued an alert about the possibility of an increased risk of amputations with canagliflozin arising from an interim analysis of the CANVAS trial.…”
Section: Other Possible Safety Concernsmentioning
confidence: 99%
“…20 While studies suggested a potential role of DPP4i as a novel therapy for several inflammatory diseases by inhibiting T cell proliferation and cytokine production, 6 7 21-27 a few cases of inflammatory arthritis potentially related to use of DPP4i have been reported. 28 The objective of this study was to estimate the risk of incident systemic AD including RA, systemic lupus erythematosus, psoriasis, psoriatic arthritis, multiple sclerosis and inflammatory bowel disease in patients with diabetes starting a DPP4i drug compared with those starting non-DPP4i oral hypoglycaemic agents. We hypothesised that patients starting a DPP4i would have a reduced risk of incident RA and other AD compared with those starting non-DPP4i drugs only.…”
Section: Introductionmentioning
confidence: 99%